PENGENALAN KONSEP SAINS TUMBUHAN MELALUI KEGIATAN PLANTING DI TK SOSIAL WAGOLA - Fauji, Asria Ali; Jeti, La; Hartati, Hartati (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to determine how planting activities can help early childhood learn about the concept of science about plants. The study was conducted at TK Sosial Wagola with a qualitative descriptive approach and the Participatory Action Research (PAR) method with a qualitative descriptive approach. The subjects of the study consisted of 10 children in group B aged 5-6 years. Data collection techniques included observation, interviews, and documentation, which were analyzed using the Miles and Huberman model. The results showed that planting activities had a positive impact on children's understanding of plant parts, growth processes, and the functions of each part. Children also showed the ability to observe, estimate, and conclude based on direct experience. In addition to improving scientific understanding, this activity also developed fine motor skills, a sense of responsibility, and concern for the environment. Children also experienced an increase in their thinking, speaking, and manual skills. And children became more active, curious, and concerned about the environment. This study suggests that activities such as planting be made a routine part of learning so that children can learn directly through experience.